G146 Can a virtual reality communication scenario be used to teach general practitioners and trainees how to recognise and manage safeguarding issues?. (12th March 2018) - Drewett, O; Hann, G; Delacroix, S; Pan, X; Fertleman, CR
Abstract : Background: Immersive reality has been demonstrated to be an exciting educational tool in clinical consultations. Research groups internationally continue to explore new uses for this technology. Safeguarding is a challenging area of practice where we must listen to the child, and tackle difficult conversations with parents. As it is unethical to ask children to role play being abused, computer generated characters could have a key role in educating healthcare professionals on how to manage difficult scenarios. Aim: To assess the interaction between doctors and a vulnerable child in a virtual reality safeguarding scenario. Methods: All doctors at several local GP practices were offered inclusion in the study in early 2017. They were placed in an immersive virtual reality consultation where we tested their ability to pick up covert safeguarding cues within a consultation with an adult patient. After the consultation, they typed up their notes electronically as they would in their day-to-day practice. We have analysed their videoed consultations with the child and used a team of experts to rank their notes on how well they managed the safeguarding concern. Results: We recruited 63 participants in total; 37 GPs and 26 trainees, and 73% identified the safeguarding element of the consultation. Following the consultation only 14% of GPs identified asking the vulnerable child in the scenario about his relationship with his father. Negative responses ranged from comments such as 'No, I thought the 'agenda' item was the letters' to 'I could/should have asked him directly if everything was ok at home' to 'I wasn't sure that I should ask Tom questions without a parent present as he is only 6'. Conclusion: The fact that 73% of participants identified the safeguarding element shows that it was identifiable within the consultation and highlights the usefulness of immersive reality as a training tool. However, it also demonstrates a need for further training to increase the recognition rate. The range of interactions with the child demonstrates that some GPs are clearly skilled at interacting with children and others less confident. Their videoed virtual reality consultations would be a useful safeguarding training tool.